Getting closer or falling apart? Euro countries after the Euro crisis - Massimo Bordignon; Nicolò Gatti; Massimiliano Gaetano Onorato (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
We study convergence and divergence dynamics in a sample of EMU countries by assembling an extensive dataset that contains information on public spending and policy outcomes in a variety of areas of government intervention including education, health, and civil justice from the early 1990s. We also focus on other important determinants of a country's economic performance such as the level of regulation of product and labor markets, as well as the trust in political institutions, quality of governance and inequality. Results show that despite divergent economic growth in the Euro periphery countries after the 2011-13 Euro crisis, the quality of services and level of regulation did not deteriorate or indeed improved, increasing convergence with the core Euro countries. However, the debt crisis dramatically worsened citizens' perceptions of quality of governance as well as the level of social trust. The very different approach followed with the Covid crisis might have mitigated the problem, but the Euro project has still shaky foundations. This calls in question its future political viability and asks for reform.
Keywords: H5; G01; P48; P51; 330; Euro; debt; crisis; convergence; reforms; governance; trust